2021
DOI: 10.1371/journal.pone.0247573
|View full text |Cite
|
Sign up to set email alerts
|

Kola nut from Cola nitida vent. Schott administered to pregnant rats induces histological alterations in pups’ cerebellum

Abstract: Kola nut (from Cola nitida) is popular in Nigeria and West Africa and is commonly consumed by pregnant women during the first trimester to alleviate morning sickness and dizziness. There is, however, a dearth of information on its effects on the developing brain. This study, therefore, investigated the potential effects of kola nut on the structure of the developing neonatal and juvenile cerebellum in the rat. Pregnant Wistar rats were administered water (as control) or crude (aqueous) kola nut extract at 400,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Interestingly, in our previous study on kola nut extract obtained from Cola nitida vent. Schott, we reported that the administration of the extract to pregnant rats induced significant impairment of motor activity and histomorphological alterations in the pups' cerebellums (Atiba et al, 2021). However, in the present study, we evaluated the post-natal motor/reflex behavior in pups following intrauterine/gestational exposure to treatment with kola nut (Cola nitida) extract.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, in our previous study on kola nut extract obtained from Cola nitida vent. Schott, we reported that the administration of the extract to pregnant rats induced significant impairment of motor activity and histomorphological alterations in the pups' cerebellums (Atiba et al, 2021). However, in the present study, we evaluated the post-natal motor/reflex behavior in pups following intrauterine/gestational exposure to treatment with kola nut (Cola nitida) extract.…”
Section: Discussionmentioning
confidence: 85%
“…Different factors have been implicated in causing adverse effects on the ability to learn and reproduce what was learned after a given time, that is, the consolidation of what was learned. Some of these factors stem from teratogens that cause body toxicity, especially in the highly sensitive brain (Atiba et al, 2021), implicating a shift or alteration in the biochemical, structural, and behavioral indices of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A signi cant number of studies that have reported higher risk of adverse pregnancy outcomes such as miscarriages (14-18), among pregnant women consuming high levels of caffeine-containing substances in pregnancy. Caffeine can cross the placenta into the amniotic uid and the fetus, resulting in adverse pregnancy outcomes (19), such as small for gestational age birth (20), and a delay in neuronal migration and gliosis (21), caused by kolanut. An understanding of patterns of kolanut use and associated factors as provided from our ndings will support the design of interventions that could target pregnant women with kolanut use in pregnancy in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Their myelinated axons terminate on neurons of the cerebellar nuclei trees, are flattened and oriented perpendicular to the parallel fiber. Cerebellar Purkinje cells (PCs) play a crucial role in motor functions and their progressive degeneration as typified by increased pyknotic nuclei in infected rat is closely associated with apoptosis ( Atiba et al., 2021 ) and motor impairments ( Kim et al., 2009 ). The degeneration of Purkinje cells within the cerebellar cortex may contribute to the loss of motor co-ordination of infected animals in the behavioral tests.…”
Section: Discussionmentioning
confidence: 99%